The Law of Complex Earth and Outer Space Systems:The Cosmolegal Proposal - Cirkovic, Elena (Taylor and Francis Group, 2025)
This book offers a paradigm-shifting exploration of lawmaking for the complex interactions between Earth systems and outer space. Drawing on complex systems science, posthuman approaches, and plural ontologies, the author proposes a reimagining of law and governance for the cosmic age. Through the “cosmolegal” perspective, this study embraces the inherent uncertainties and complexities of Earth-space interactions. From Arctic methane craters to orbital debris, the book weaves together scientific insights, landscape architecture, legal theory, and doctrine to address pressing environmental challenges that span Earth and beyond. While legal scholarship has increasingly engaged with Earth System Science, it typically treats outer space as distinct from Earth’s environment. However, Earth’s existence and complex systems are fundamentally intertwined with and emerge from outer space. This book argues that a legal framework for Earth’s systems needs to include outer space. At its core, the book advocates for a “complexification” of law, calling for greater epistemic humility in legal thought and practice. Thoughtful and provocative, this work invites readers to reconsider fundamental assumptions about law, nature, and agency beyond the human in an era of planetary change. The cosmolegal approach aims to shift legal imagination and understanding, positioning human law as just one of many actors within the cosmos. This original work will appeal to scholars of legal theory and environmental law, as well as those interested in posthumanism, ecology, and materialism.